A Study on Sistani Satirical Proverbs - Fatemeh Elhami (مطالعات زبانی و بلاغی)
This study aims to identify the styles of satirical language in proverbs of Sistan. Sistani dialect is related to the people who live in northeast of Sistan and Baluchestan province. Sistan with thousands of years antiquity is a land of ancient language, culture and customs. There are lots of proverbs in this dialect which prove this matter. Collection of data is done by library method and interview with several informants. Descriptive-analytical methodology is used in this research. Among around seven hundred collected proverbs only the ones with satirical language aspects were analyzed. By analyzing the contrast and difference between discourse and situation in the proverbs of this study, around seventeen satirical components from hyperbole, inner conflict, comparing congruous matters, oxymoron, irony of situation, hyperbolic compliment were identified. The results of this study showed that the common speech in most proverbs and local adages of Sistani people is satirical, ironic and sarcastic language which is resided pleasantly in the most summarized speech.